Psychosocial factors associated with health behaviors in pregnant women of advanced maternal age in Korea - Jeon, Songi; Noh, Wonjung (Frontiers in Public Health, 2023)
Objectives To determine the association between psychosocial factors and health-promoting and health-impairing behaviors in pregnant women of advanced maternal age (AMA) in Korea. Design A cross-sectional survey study. Setting Online survey. Samples A total of 217 pregnant women aged 35 and older agreed to participate in the study, with 207 participants completing the self-report questionnaires. Methods We collected self-reported data on demographic, obstetric, and psychosocial factors and prenatal health behaviors using standardized measures. We conducted a descriptive analysis of the collected data and a linear regression to identify significant associations with health-promoting and health-impairing behaviors. Results We found that maternal–fetal attachment (β = 0.43, p < 0.001) and “social atmosphere” of pregnancy stress (β = 0.13, p = 0.047) were positively associated with prenatal health-promoting behaviors. We found that artificial conception (β =-0.16, p = 0.011) was negatively associated with prenatal health-impairing behaviors and that multiparity (β = 0.23, p = 0.001) and “maternal role” of pregnancy stress (β = 0.27, p = 0.003) positively associated with prenatal health-impairing behaviors. Conclusion Health-impairing behaviors of pregnant AMA women need assessment and the importance of health-promoting behaviors for maternal and infant health need reinforcing. We recommend pregnancy stress assessments at prenatal checkups and stress relief interventions that consider cultural differences and contexts rather than standardized interventions.